The relationship between wasting and stunting: a retrospective cohort analysis of longitudinal data in Gambian children from 1976 to 2016. - Schoenbuchner, SM; Dolan, C; Mwangome, M; Hall, A; Richard, SA; Wells, JC; Khara, T; Sonko, B; Prentice, AM; Moore, SE (Oxford University Press, 2019)
Background The etiologic relationship between wasting and stunting is poorly understood, largely because of a lack of high-quality longitudinal data from children at risk of undernutrition.